CHARACTER BUILDING IN THE EFFORT TO PREVENT THE THREE SINS OF EDUCATION THROUGH THE TEACHING CAMPUS PROGRAM - Rakhmadani, Syeni; Yuditya Wardhana; Barokah, Ihda Lailatul (Pasundan International of Community Services Journal (PICS-J), 2025)
The high number of cases of bullying, intolerance and sexual violence in Indonesia is a major challenge for the world of education. These three problems make it 3 sins in education where cases of bullying make Indonesia one of the countries with the highest cases of bullying, cases of intolerance have also spread in the world of education from high schools to elementary schools and cases that are no less worrying are cases of sexual violence with the highest cases experienced by children aged 6-12 years as much as 33% and the lowest in children aged 0-5 years as much as 7.7%. The increasing number of cases of the 3 sins in the world of education is due to the lack of character of the students. Community Service which was held on November 23, 2024 at MetroTimur 8 Public Elementary School was carried out using video learning and discussion methods with the aim of instilling character in preventing the 3 sins of education